Salt composition of the waters of the Bureya reservoir - Vladimir P. Shesterkin; Nina M. Shesterkina (Водное хозяйство России: проблемы, технологии, управление)
Significance of the work lies in the need to study the salt composition of the Bureya reservoir water from the beginning of filling, which is important for predicting the water quality of reservoirs in the Amur basin that are to be designed. The objective is to evaluate content of main ions in the water of the Bureya reservoir, and to identify factors determining their spatial and temporal variability.